Catalytic materials of oxygen-deficient Pt(111 / 200) composite crystal plane atomically supported rod-shaped La-Al2O3, their preparation methods and applications

CN122424811BActive Publication Date: 2026-09-04CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610903317.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-09-04
Estimated Expiration
2046-06-23

AI Technical Summary

Technical Problem

[0005]综上,现有技术公开了较多Pt基尾气处理催化剂,但现有催化剂的贵金属负载量仍较高、且低温下的催化氧化性能以及耐老化性能有待进一步提升

Benefits of technology

[0062] 1. This invention provides a novel catalyst using rod-shaped La-Al2O3 as a support and loaded with PtM composite materials with special composite crystal faces, atomic-level loading and oxygen defects. Based on the combined synergy of the material's physicochemical structure, it can achieve excellent catalytic oxidation activity and stability of automobile exhaust gas even at low loading; and the material has better low-temperature start-up activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122424811B_ABST
    Figure CN122424811B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of automobile exhaust purification catalytic materials, and particularly relates to a kind of oxygen defect Pt (111 / 200) composite crystal face atomic level PtM supported rod-shaped La-Al2O3 catalytic materials and its preparation method and application, wherein the catalytic material includes carrier and its supported active ingredient, the carrier is rod-shaped La-Al2O3;Active ingredient is atomic level PtM composite material, Pt and M in it exist in the form of nano-particle, single atom, diatomic and few atom cluster;And Pt exists 111 and 200 composite crystal face;M includes at least one of Pd, Co, Mn and Cu;The carrier and / or active ingredient has oxygen defects.The catalyst improves the molecular activation capacity, low-temperature catalytic oxidation activity and anti-aging stability, and can improve the automobile exhaust catalytic oxidation treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of automotive exhaust purification catalytic materials, specifically relating to an oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3 catalytic material, its preparation method, and its application fields. Background Technology

[0002] Diesel vehicles, with their advantages of high fuel efficiency, economy, durability, and high safety, have a broad market development potential. However, diesel vehicle exhaust contains carbon monoxide (CO) and nitrogen oxides (NOx). x The content of diesel fuel and hydrocarbons (HC) in diesel vehicles is much higher than that in gasoline vehicles, posing a great threat to the ecological environment and human health. Therefore, effectively controlling diesel vehicle pollution emissions is of great significance for its market promotion and application.

[0003] Existing catalytic oxidation catalysts for automotive exhaust mainly include noble metal-based catalysts, non-noble metal oxide catalysts, and rare earth modified catalysts. Noble metal-based catalysts primarily include platinum, palladium, rhodium single metals, and their alloys. Non-noble metal oxide catalysts mainly include manganese-based catalysts (MnO₂). x Rare earth modified catalysts include copper-chromium based, cobalt-based, iron-based composite oxides, perovskite-type composite oxides, etc. Rare earth modified catalysts mainly include CeO2 and Ce-Zr composite oxides.

[0004] For example, patent document CN105188916A discloses a diesel exhaust gas oxidation catalyst for purifying exhaust gas from a diesel engine, comprising an alumina-based support, Pt supported on the alumina-based support, Pd supported on the alumina-based support, and at least one additional element selected from alkali metals and alkaline earth metals supported on the alumina-based support. As another example, patent document CN119951543A discloses a diesel oxidation catalyst and its preparation method; this diesel oxidation catalyst comprises a cordierite honeycomb ceramic support and an active coating attached to the surface of the cordierite honeycomb ceramic support, the active coating comprising hydroxyapatite, and the hydroxyapatite being loaded with noble metals, including Pt and Pd metals.

[0005] In summary, existing technologies have disclosed a number of Pt-based tail gas treatment catalysts, but the noble metal loading of existing catalysts is still relatively high, and their catalytic oxidation performance at low temperatures and aging resistance need to be further improved. Summary of the Invention

[0006] To address the problems existing in the prior art, the primary objective of this invention is to provide a catalytic material of oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3, aiming to provide a catalyst with low loading, low-temperature catalytic activity, and aging resistance.

[0007] The second objective of this invention is to provide a method for preparing the aforementioned catalytic material and its application in the oxidation catalysis of automobile exhaust.

[0008] A catalytic material of rod-shaped La-Al2O3 supported on atomic-level PtM with oxygen-deficient Pt(111 / 200) composite crystal plane, including the support and the active component supported thereon, wherein the support is rod-shaped La-Al2O3;

[0009] The active ingredient is an atomic-level PtM composite material, in which Pt and M exist in the form of nanoparticles, single atoms, diatomic particles and few-atom clusters; and Pt has 111 and 200 composite crystal planes; M includes at least one of Pd, Co, Mn and Cu.

[0010] The carrier and / or active ingredient have oxygen defects.

[0011] This invention innovatively uses rod-shaped La-Al2O3 as a support and loads atomic-level PtM composite material on it. Combined with the characteristics of Pt's 111 and 200 composite crystal planes and overall oxygen defects, this achieves synergy, which can improve the catalytic oxidation activity of automobile exhaust gas, improve its low-temperature catalytic oxidation capability, and further improve its structural stability and aging resistance. Moreover, the catalytic material described in this invention can achieve excellent catalytic performance at a relatively low loading.

[0012] In this invention, the content of La in the rod-shaped La-Al2O3 is 1~2 wt.%; the diameter is 8~30 nm; and the aspect ratio can be 3~8.

[0013] In the PtM composite material, the weight ratio of Pt / M is 3:1 to 6:1; preferably 4:1 to 6:1, and more preferably 5:1.

[0014] In the catalytic material, the loading of PtM composite material is 0.8~1.6 Wt.%; more specifically, it can be 1~1.4 Wt.%.

[0015] The relative exposure ratio of Pt(200) crystal planes in the catalytic material is 20-30%.

[0016] This invention also provides a method for preparing the oxygen-deficient Pt(111 / 200) composite crystal plane atomically supported rod-shaped La-Al2O3 catalytic material, the steps of which include:

[0017] Step 1:

[0018] Rod-shaped La-Al2O3 was thermally modified to obtain a modified support;

[0019] The aforementioned thermal modification is a programmed variable oxygen potential defect activation thermal modification, which includes a high oxygen atmosphere thermal modification process and a low oxygen atmosphere thermal modification process; wherein, the oxygen content of the high oxygen atmosphere is 10~100v%; and the oxygen content of the low oxygen atmosphere is below 5v%.

[0020] Step 2:

[0021] The modified carrier and the M source are impregnated to obtain a carrier composite with M; wherein the impregnation treatment includes a pressure-switching impregnation process and a pulsed ultrasonic impregnation process; wherein the pressure-switching impregnation process includes a periodic impregnation process under pressure P1 and an impregnation process under pressure P2; pressure P1 is negative pressure; pressure P2 is atmospheric pressure or positive pressure;

[0022] Step 3:

[0023] The composite M support and Pt colloid were mixed and deposited under alkaline conditions to obtain the composite Pt-M support.

[0024] Step 4:

[0025] The catalytic material was prepared by annealing the composite Pt-M support at a temperature of 150~250℃.

[0026] In this invention, the challenges in material preparation lie in how to rationally induce (111 / 200) composite crystal planes and form atomic-level PtM, and how to avoid 200 crystal plane transformation and atomic-level PtM agglomeration. To address these challenges, this invention innovatively uses rod-shaped La-Al2O3 as a substrate, pre-treating it with programmed oxygen potential defect activation thermal modification. This is followed by a two-stage composite method: first M-Pt, then Pt colloid, further enhanced by combined annealing and temperature control. This unexpectedly achieves synergy, successfully inducing atomic-level loading of M-Pt, avoiding the formation of multi-atomic clusters, and inducing abundant (111 / 200) composite crystal planes and in-situ defects, while improving the proportion of 200 crystal planes. Research in this invention shows that the preparation method yields a novel material with the aforementioned physicochemical characteristics, and this material unexpectedly exhibits excellent oxidation activity and stability in automotive exhaust gases.

[0027] In this invention, the hybridization of La in rod-shaped La-Al2O3 and the rod-shaped structure are combined with other preparation processes and are one of the key factors in inducing atomic-level loading of M and Pt and inducing (111 / 200) composite crystal planes. On this basis, further thermal modification processes can further enhance the induction of atomic-level loading of M and Pt and (111 / 200) composite crystal planes.

[0028] In step 1, the high-oxygen atmosphere is a mixture of air, oxygen, oxygen-dilution gas, or air-dilution gas.

[0029] The low-oxygen atmosphere is at least one of nitrogen and rare gases;

[0030] The thermal modification process includes a periodic high-oxygen atmosphere thermal modification process and a low-oxygen atmosphere thermal modification process; the time for a single high-oxygen atmosphere thermal modification is 10~60 min; the time for a single low-oxygen atmosphere thermal modification is 10~60 min.

[0031] In the thermal modification process of this invention, a thermal modification cycle consists of first thermal modification in a high-oxygen atmosphere and then thermal modification in a low-oxygen atmosphere.

[0032] The number of cycles for the high-oxygen atmosphere thermal modification process and the low-oxygen atmosphere thermal modification process is 1 to 5.

[0033] The temperature for the thermal modification process is 300~500℃, and can be further set to 350~450℃;

[0034] The total time for the thermal modification process is 2-4 hours.

[0035] In this invention, the M source is first leached out, and then Pt is composited in colloidal form. This is beneficial for combining with other processes to further enhance the atomic-level loading of M and Pt and the induction of the (111 / 200) composite crystal plane.

[0036] The M source is a water-soluble salt of M metal and / or a complex of M metal;

[0037] The M source includes at least one of the following: chloride, nitrate, acetate, acetylacetone salt, ammonia complex salt, or organic amine complex of the M metal;

[0038] The impregnation system also contains a complexing agent and a slow-release alkali source.

[0039] The complexing agent can be at least one of ammonia, ethylenediamine, citric acid, ethanolamine, or ethylene glycol; the slow-release alkali source can be at least one of urea, hexamethylenetetramine, or ammonium carbonate; the weight ratio of M source and slow-release alkali source can be 1:0.5~5. The pH of the impregnation process can be 7.5~8.5.

[0040] During the impregnation process, the pressure of P1 is -0.06 to -0.10 MPa;

[0041] The immersion time under a single P1 pressure is 5~30 min, and the immersion time under a single P2 pressure is 5~30 min;

[0042] In this invention, immersion under pressure P1 followed by immersion under pressure P2 constitutes one immersion cycle.

[0043] The number of cycles in the pressure-variable impregnation process is 1 to 5.

[0044] The power of the pulsed ultrasonic impregnation treatment is 100~500W, each ultrasonic treatment lasts 1~10 minutes, with an interval of 1~10 minutes, and the cycle is repeated 1~6 times.

[0045] In this invention, after pulsed ultrasonic impregnation treatment, aging treatment can be optionally performed, wherein the aging temperature can be 40~90℃ and the aging time can be 2~8h.

[0046] In this invention, Pt colloids are obtained by a reduction reaction of Pt source, alkali and ethylene glycol;

[0047] The Pt source is at least one of chloroplatinic acid, hydrated chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, platinum nitrate, or platinum acetylacetonate.

[0048] The alkali is at least one of NaOH, KOH, LiOH, ammonia, sodium carbonate, or potassium carbonate;

[0049] The weight ratio of Pt source, alkali and ethylene glycol is 1:0.2~3:30~200; it can be further 1:0.8~1.2:80~120.

[0050] The temperature of the reduction reaction is 120~160℃, preferably 130~150℃; and even more preferably 135~145℃.

[0051] The reduction reaction takes 2 to 5 hours.

[0052] In the preparation of the Pt colloid, the alkali is added dropwise to the Pt source / ethylene glycol solution in the form of an alkali / ethylene glycol solution, and the dropping rate is controlled at 0.1~2.0 mL / min to avoid the local strong alkaline environment causing rapid nucleation and aggregation of Pt species.

[0053] In this invention, in step 3, the pH under alkaline conditions is 8.5~10.5;

[0054] The deposition temperature is 70~90℃; the deposition time is 1~5h.

[0055] In step 4, the annealing atmosphere is at least one of Ar, N2, and He; the annealing temperature is preferably 180~220℃. The annealing time is 1~4h, and more preferably 2~3h.

[0056] Furthermore, the process includes a pre-annealing step before annealing, wherein the pre-annealing atmosphere can be air. The pre-annealing temperature is 80~120℃; the pre-annealing time can be 0.5~2.5h.

[0057] The present invention also provides an application of the catalytic material described above, using it for the catalytic oxidation of automobile exhaust.

[0058] The aforementioned application refers to vehicle exhaust containing at least one gaseous pollutant selected from CO, NO, C3H6, and C3H8.

[0059] The application conditions described in this invention can be reasonably adjusted as needed.

[0060] For example, before application, the catalytic material can be thermally activated, and the thermal activation temperature can be 400~600℃.

[0061] Beneficial effects

[0062] 1. This invention provides a novel catalyst using rod-shaped La-Al2O3 as a support and loaded with PtM composite materials with special composite crystal faces, atomic-level loading and oxygen defects. Based on the combined synergy of the material's physicochemical structure, it can achieve excellent catalytic oxidation activity and stability of automobile exhaust gas even at low loading; and the material has better low-temperature start-up activity.

[0063] 2. The present invention also provides a method for preparing the catalytic material, which uses rod-shaped La-Al2O3 as a substrate and combines thermal modification, two-stage loading of M followed by Pt colloid and low-temperature annealing process to induce the material with special atomic size, composite crystal facets and defects in situ. The material can unexpectedly exhibit excellent oxidation activity and stability of automobile exhaust gas. Attached Figure Description

[0064] Figure 1 The graph shows the CO catalytic oxidation performance of the PtPd / La-Al2O3 catalyst prepared in Example 1.

[0065] Figure 2 The graph shows the NO catalytic oxidation performance of the PtPd / La-Al2O3 catalyst prepared in Example 1.

[0066] Figure 3 The graph shows the C3H6 catalytic oxidation performance of the PtPd / La-Al2O3 catalyst prepared in Example 1.

[0067] Figure 4 The graph shows the C3H8 catalytic oxidation performance of the PtPd / La-Al2O3 catalyst prepared in Example 1.

[0068] Figure 5 PtPd / La-Al2O prepared in Example 1 3、 EPR diagrams of the catalysts prepared in Comparative Examples 1, 2, and 3.

[0069] Figure 6This is a TEM image of the PtPd / La-Al2O3 catalytic material prepared in Example 1.

[0070] Figure 7 This is a TEM image of the catalytic material prepared in Comparative Example 4.

[0071] Figure 8 The image shows aberration-corrected HAADF-STEM image of the PtPd / La-Al2O3 catalytic material prepared in Example 1.

[0072] Figure 9 The image shows the aberration-corrected HAADF-STEM image of the catalytic material prepared in Comparative Example 7.

[0073] Figure 10 The images shown are TEM or HRTEM images of the PtPd / La-Al2O3 catalytic material prepared in Example 1.

[0074] Figure 11 TEM or HRTEM image of the catalytic material prepared for Comparative Example 15. Detailed Implementation

[0075] The following specific embodiments are intended to further illustrate the content of the present invention, rather than to further limit the scope of protection of the claims of the present invention.

[0076] Unless otherwise specified, the reagents used in the following examples are commercially available reagents purchased directly from the market.

[0077] The preparation steps of the material described in this invention can be as follows:

[0078] Step 1:

[0079] Rod-shaped La-Al2O3 was thermally modified to obtain a modified support;

[0080] The thermal modification is a programmed oxygen potential defect activation thermal modification, which includes an air activation stage and a low oxygen potential defect induction stage performed sequentially.

[0081] The atmosphere of the air activation stage is at least one of air, oxygen, or an oxygen / inert gas mixture, used to expose and regulate La–O–Al sites and surface hydroxyl sites;

[0082] The low-oxygen potential atmosphere is at least one of Ar, N2, vacuum or low-concentration H2 / Ar atmosphere.

[0083] The process of first activating with air and then inducing low oxygen potential defects constitutes a variable gas treatment cycle.

[0084] The thermal modification temperature is 300~500℃, and the total thermal modification time is 2~4h. After the thermal modification is completed, the surface is cooled to room temperature in an inert atmosphere or a low oxygen potential atmosphere to obtain a modified rod-shaped La-Al2O3 support (modified support) with La–O–Al unsaturated coordination sites, hydroxyl defect sites and oxygen vacancies on the surface.

[0085] Step 2:

[0086] The modified carrier and the M source are impregnated to obtain a carrier composite with M; wherein the impregnation treatment includes a pressure-switching impregnation process and a pulsed ultrasonic impregnation process; wherein the pressure-switching impregnation process includes a periodic impregnation process under pressure P1 and an impregnation process under pressure P2; pressure P1 is negative pressure; pressure P2 is atmospheric pressure or positive pressure;

[0087] Furthermore, the thermally modified rod-shaped La-Al2O3 was dispersed in a mixed solution containing an M source, a complexing agent, and a slow-release alkali source. The solution was then permeated and impregnated under alternating vacuum and atmospheric pressure conditions, and pulsed ultrasonic treatment was performed to allow the M species to fully penetrate the pores on the surface of the rod-shaped La-Al2O3, the gaps between the rod-shaped particles, and the vicinity of oxygen vacancy sites. Subsequently, the solution was heated and aged to allow the slow-release alkali source to gradually decompose and release alkali species, inducing the selective hydrolysis deposition and confined anchoring of the M species near La–O–Al sites, hydroxyl vacancy sites, or oxygen vacancy precursors, thus obtaining a composite M carrier.

[0088] The complexing agent is at least one of ammonia, ethylenediamine, citric acid, ethanolamine, or ethylene glycol; the slow-release alkali source is at least one of urea, hexamethylenetetramine, or ammonium carbonate; the vacuum-atmospheric pressure alternation process is maintained at -0.06 to -0.10 MPa for 5 to 30 minutes, followed by restoring to atmospheric pressure and maintaining for 5 to 30 minutes, repeated 1 to 5 times; the power of the pulsed ultrasonic impregnation process is 100 to 500 W, each ultrasonic treatment lasts 1 to 10 minutes, with an interval of 1 to 10 minutes, repeated 1 to 6 times; the aging temperature is 40 to 90°C, and the aging time is 2 to 8 hours.

[0089] Step 3:

[0090] The composite M support and Pt colloid were mixed and deposited under alkaline conditions to obtain the composite Pt-M support.

[0091] Step 4:

[0092] The catalytic material was prepared by annealing the composite Pt-M support at a temperature of 150~250℃.

[0093] Example 1

[0094] Step 1:

[0095] 1 g of La-Al2O3 powder (La content 1.5 wt%, rod diameter 8~30 nm) was used as a support for pretreatment: The temperature was increased to 400 °C at a rate of 5 °C / min under air atmosphere and held for 1 h; then, a pulsed oxygen potential treatment (gas-switching treatment) was performed at 400 °C, periodically switching between air and Ar atmospheres; each cycle included 20 min of air atmosphere treatment and 20 min of Ar atmosphere treatment, repeated 3 times. After treatment, the mixture was naturally cooled to room temperature under Ar atmosphere to obtain the modified La-Al2O3 support.

[0096] Step 2:

[0097] Weigh out PdCl2·6H2O (a hydrochloric acid solution of PdCl2, wherein the mass fraction of Pd is 0.2%) and dissolve it in 30 mL of deionized water. Under stirring, slowly add dilute ammonia water dropwise to adjust the pH of the solution to 8 (±0.1). Add urea (PdCl2 to urea weight ratio of 1:1) to the above solution and stir until completely dissolved to obtain a mixed impregnation solution containing a Pd source, an ammonia complexing agent, and a urea slow-release alkali source.

[0098] The modified La-Al2O3 support obtained in step 1 was added to the above mixed impregnation solution. After stirring and dispersing for 30 min, the dispersion was treated under vacuum conditions. The vacuum degree was controlled at -0.08 MPa and maintained for 10 min. Then, the pressure was restored to normal and maintained for 10 min. The vacuum-normal pressure cycle was repeated 3 times to obtain the dispersion.

[0099] The dispersion was then subjected to pulsed sonication (ultrasonic power of 200W) for 10 minutes each time, with a 5-minute interval, for 3 cycles. After sonication, the system was heated to 80℃ and reacted for 4 hours under stirring. It was then dried overnight at 60℃ in an oven and ground into a fine powder to obtain Pd / La-Al2O3.

[0100] Step 3:

[0101] Weigh 0.25 g of H2PtCl6·6H2O into a round-bottom flask, add 12.5 mL of EG (ethylene glycol) and stir until completely dissolved to obtain solution A. Slowly add 12.5 mL of 0.5 M NaOH / EG to solution A and stir for 30 min. Place the round-bottom flask in an oil bath at 140 °C for 3 h and cool to room temperature to obtain Pt colloid.

[0102] Step 4:

[0103] Place the uniformly ground Pd / La-Al2O3 in a round-bottom flask, add 100 mL of EG and stir until homogeneous. Slowly add 2.65 mL of the prepared Pt colloid (Pt / Pd weight ratio of 5:1; and the total weight of Pt / Pd is 1.2% of the carrier weight) at a dropping rate of 1.0 mL / min. Adjust the pH of the solution to 9.5 with 0.5 M NaOH / EG, stir for 30 min, and then keep it in an oil bath at 80℃ for 3 h.

[0104] Step 5:

[0105] After washing the reacted material with water and centrifuging it 5 times, it was dried in an oven at 60℃ for 8 hours to obtain Pt-Pd / La-Al2O3.

[0106] Step 6:

[0107] The Pt-Pd / La-Al2O3 material obtained in step 5 was ground and placed in a muffle furnace. Under an air atmosphere, the temperature was increased to 100°C at a rate of 5°C / min, held for 1 hour, and then naturally cooled to room temperature. The resulting powder was then placed in a tube furnace and annealed under an Ar atmosphere at a rate of 5°C / min to 200°C. After holding for 2 hours, the temperature was naturally cooled to room temperature to complete the annealing process, yielding Pt,Pd alloy-supported alumina (Pt...). x Pd y / La-Al2O3) catalyst (newly prepared catalyst, also known as fresh catalyst).

[0108] Step 7: Thermocatalytic performance testing

[0109] Pt obtained x Pd y La-Al2O3 powder was compressed into tablets, and the catalyst was sieved. Approximately 0.5 g of catalyst with a particle size of 40-60 mesh was selected as the test medium, with a compressed volume of 0.38 mL. The catalytic oxidation activity of the catalyst was evaluated on a multifunctional micro-quartz tube fixed-bed continuous reaction apparatus. A pre-calibrated mass flow meter was used to control the gas flow rate in each gas path, and thermocouples were inserted into the fixed reaction bed to monitor the real-time reaction temperature. The simulated diesel vehicle exhaust gas composition was: NO (500 ppm), CO (500 ppm), C3H6 (200 ppm), C3H8 (100 ppm), O2 (8%), H2O (10%), and N2 as the carrier gas, with a space velocity of 300,000 h⁻¹. -1 Simulated gas is introduced, and the reaction is carried out under continuous heating conditions. The residual amount of each pollutant in the exhaust gas is detected at the outlet of the reaction tube. After the prepared reaction atmosphere is introduced until the gas equilibrium is reached, the temperature is continuously increased from 100℃ to 500℃ for activation treatment, then cooled to 100℃. After the temperature stabilizes, the temperature is continuously increased from 100℃ to 500℃ for testing.

[0110] The catalyst aging process involves placing the sample in a muffle furnace and heating it from room temperature to 650°C at a rate of 3°C / min, holding it at that temperature for 100 hours. This results in an aged catalyst, which is then tested using the same method as a fresh catalyst.

[0111] Example 2

[0112] Compared with Example 1, the only difference is that in step 4, the amount of Pt is changed so that the mass ratio of Pt to Pd is 4:1 and the weight percentage of PtPd relative to the carrier is 1.0%. All other operations and parameters are the same as in Example 1.

[0113] Example 3

[0114] Compared with Example 1, the only difference is that in step 4, the amount of Pt is changed so that the mass ratio of Pt to Pd is changed to 6:1 and the weight percentage of PtPd relative to the carrier is 1.4%. All other operations and parameters are the same as in Example 1.

[0115] Example 4

[0116] Compared with Example 1, the only difference is that the oil bath temperature in step 3 is changed to 130°C and the holding time at this temperature is 5 hours. In step 4, the solution pH is adjusted to 10.5 and the oil bath temperature is changed to 70°C. All other operations and conditions are the same as in Example 1.

[0117] Example 5

[0118] Compared with Example 1, the only difference is that the oil bath temperature in step 3 is changed to 150°C, the solution pH is adjusted to 8.5 and the oil bath temperature is changed to 90°C in step 4, and all other operations and conditions are the same as in Example 1.

[0119] Example 6

[0120] Compared with Example 1, the only difference is that the Ar atmosphere annealing temperature in step 6 is adjusted to 150°C and the time is 3.5h. All other operations and conditions are the same as in Example 1.

[0121] Example 7

[0122] Compared with Example 1, the only difference is that the Ar atmosphere annealing temperature in step 6 is adjusted to 250°C and the time is 1.5h. All other operations and conditions are the same as in Example 1.

[0123] Example 8

[0124] Compared with Example 1, the only difference is that the palladium source in step 1 is replaced with a copper source (copper chloride), and all other operations and conditions are the same as in Example 1.

[0125] Example 9

[0126] Compared with Example 1, the only difference is that the palladium source in step 1 is replaced with a cobalt source (cobalt chloride), while the other operations and conditions are the same as in Example 1.

[0127] Example 10

[0128] Compared with Example 1, the only difference is that the palladium source in step 1 is replaced with a manganese source (manganese chloride), while the other operations and conditions are the same as in Example 1.

[0129] Comparative Example 1

[0130] Compared with Example 1, the only difference is that in step 1, the carrier does not undergo a heat treatment process and directly proceeds to step 2 and subsequent treatments. All other operations and parameters are the same as in Example 1.

[0131] Comparative Example 2

[0132] Compared with Example 1, the only difference is that in step 1, no gas conversion treatment was performed, and after the temperature was raised to 400°C, it was only kept warm in an air atmosphere. The total holding time and other operations were the same as in Example 1.

[0133] Comparative Example 3

[0134] Compared with Example 1, the only difference is that in step 1, no gas-changing treatment was performed, and after the temperature was raised to 400°C, it was only kept at a constant temperature in an Ar atmosphere. The total holding time and other operations were the same as in Example 1.

[0135] Comparative Example 4

[0136] Compared with Example 1, the only difference is that in step 1, the support is replaced with a γ-Al2O3 support.

[0137] Comparative Example 5

[0138] Compared with Example 1, the only difference is that in step 1, the support is replaced with an α-Al2O3 support.

[0139] Comparative Example 6

[0140] Compared with Example 1, the only difference is that the support in step 1 is replaced with γ-Al2O3 support, and in step 2, La(NO3)3·6H2O is added in addition. The amount of La introduced is the same as that introduced by the support in Example 1.

[0141] Comparative Example 7

[0142] Compared to Example 1, the only difference is that steps 2 to 4 are replaced with the traditional impregnation method and sodium borohydride reduction process. The replaced steps are as follows: After step 1, the modified La-Al2O3 powder and the aqueous solution containing PdCl2·6H2O and H2PtCl6·6H2O are stirred evenly and then sonicated for 3 hours. The amounts of Pd and Pt are the same as in Example 1. Then, NaBH4 aqueous solution (twice the theoretical amount of Pt and Pd to be reduced) is slowly added to the system for reduction. After reduction, the powder is centrifuged and washed, dried overnight at 60°C in an oven, and ground to obtain fine Pt-Pd / La-Al2O3 powder. Then, it is processed in step 6. The ratio of Pt and Pd and the total loading, as well as other operations and parameters, are the same as in Example 1.

[0143] Comparative Example 8

[0144] Compared with Example 1, the difference is that no Pd source is added in step 2, and the amount of remaining Pt is the same as the total weight of PtPd elements in Example 1. Other operations and parameters are the same as in Example 1.

[0145] Comparative Example 9

[0146] Compared with Example 1, the only difference is that in step 2, the impregnation process does not employ pressure swing treatment; the entire impregnation process is carried out under normal pressure. The replaced step is as follows: the modified La-Al2O3 support obtained in step 1 is added to the above mixed impregnation solution, and the mixture is stirred and dispersed under normal pressure for 1.5 hours to obtain a dispersion. All other operations and parameters are the same as in Example 1.

[0147] Comparative Example 10

[0148] Compared with Example 1, the only difference is that pulsed ultrasound processing is not performed in step 2, while other operations and parameters are the same as in Example 1.

[0149] Comparative Example 11

[0150] Compared with Example 1, the only difference is that in step 2, the pulse ultrasound processing method is replaced with conventional ultrasound. The condition for conventional ultrasound is continuous ultrasound for 30 minutes. All other operations and parameters are the same as in Example 1.

[0151] Comparative Example 12

[0152] Compared with Example 1, the only difference is that step 2 is not performed. Instead, the same amount of Pd as in step 2 is added to step 3 and loaded together with Pt. All other operations and parameters are the same as in Example 1.

[0153] Comparative Example 13

[0154] Compared with Example 1, the only difference is that after step 1, steps 3 and 4 are performed first, followed by step 2, then step 5 and subsequent operations. All other operations and parameters are the same as in Example 1.

[0155] Comparative Example 14

[0156] Compared with Example 1, the only difference is that Pt colloid is not added in step 4, the amount of remaining Pd is the same as the total weight of PtPd elements in Example 1, and other operations and parameters are the same as in Example 1.

[0157] Comparative Example 15

[0158] Compared with Example 1, the only difference is that in step 6, the annealing temperature is 300°C, and all other operations and parameters are the same as in Example 1.

[0159] The test results for each case are shown in Tables 1 and 2:

[0160] Table 1: Catalytic results of fresh catalyst:

[0161] Table 2: Catalytic results of the aged catalyst:

[0162] Figures 1-4 The results of the fresh catalyst prepared in Example 1 and the catalytic degradation effect after aging show that the catalyst has excellent catalytic activity and anti-aging stability.

[0163] Figure 5 The EPR spectra of the samples prepared in Example 1 and Comparative Examples 1-3 are shown. Figure 5 As can be seen, EPR signals related to oxygen vacancies can be observed around g=2.003, with the signal intensity of Example 1 being significantly higher than that of Comparative Examples 1, 2, and 3. Comparative Example 1 did not undergo thermal modification of the carrier, Comparative Example 2 was only treated with an air atmosphere, and Comparative Example 3 was only treated with an Ar atmosphere; their oxygen vacancy signals were all weak, indicating that the aforementioned gas-modification treatment helps to construct beneficial defect structures.

[0164] Combined with appendix Figure 6 and Figure 7 It can be seen that the PtPd / La-Al2O3 catalytic material prepared in Example 1 maintains a distinct rod-shaped support morphology, with PtPd metal species relatively uniformly dispersed on the surface of the rod-shaped La-Al2O3 and in the interparticle regions; while in Comparative Example 4, using γ-Al2O3 as the support, the support mainly exhibits an irregular particle agglomeration morphology. This indicates that the pre-formed rod-shaped La-Al2O3 support is beneficial for providing stable metal anchoring points and dispersion interfaces.

[0165] Combined with appendix Figure 8 and Figure 9 As can be seen from the aberration-corrected HAADF-STEM image of Example 1, numerous discrete atomic-level high-brightness scattering points can be observed on the carrier surface and interface region, indicating that some Pt ​​and / or Pd exist in the form of atomically dispersed noble metal species. In contrast, after using the conventional co-impregnation-sodium borohydride reduction process in Comparative Example 7, the high-brightness areas are more characterized by particle or cluster aggregation, and the number of discrete atomic-level high-brightness points is significantly reduced. This demonstrates that the Pd defect confinement pre-anchoring and Pt colloidal directional deposition process of the present invention is more conducive to the formation of atomic-level noble metal loading structures.

[0166] Combined with appendix Figure 10 and Figure 11 It can be seen that in Example 1, lattice fringes of approximately 0.222 nm and 0.199 nm can be observed in the PtPd nanoparticles, corresponding to the Pt(111) and Pt(200) related crystal planes, respectively, indicating that the process of the present invention can induce the formation of Pt(111) / Pt(200) composite crystal planes. In contrast, after annealing at 300 °C, Comparative Example 15 mainly observed Pt(111) related crystal planes, and no obvious Pt(200) crystal plane features were observed, indicating that excessively high annealing temperatures can easily lead to the reduction or reconstruction of high-energy Pt(200) crystal planes. This shows that the low-temperature Ar atmosphere annealing used in Example 1 is more conducive to maintaining the Pt(111 / 200) composite crystal planes and highly dispersed metal structure.

[0167] As can be seen from Examples 1 to 10, by innovatively using rod-shaped La-Al2O3 as a substrate, combined with programmed variable oxygen potential defect activation thermal modification, a two-stage composite method of first Pd and then Pt colloids, and low-temperature annealing, a synergistic effect can be unexpectedly achieved, optimizing the defects, crystal planes, and atomic-level structure of the material, thereby improving the cold start treatment effect and anti-aging effect of exhaust gas.

[0168] As can be seen from Example 1 and Comparative Examples 1, 2, and 3, the lack of thermal modification or the use of conventional air / inert gas heat treatment both resulted in a significant decrease in catalytic performance. This demonstrates that the combined application of the programmed oxygen potential defect activation thermal modification and process of the present invention can, for example, improve the catalytic activity of exhaust gas.

[0169] As shown in Examples 1 and Comparative Examples 4-6, ordinary γ-Al2O3, α-Al2O3, and subsequently La-loaded γ-Al2O3 cannot replace the modified rod-shaped La-Al2O3. This indicates that the modified rod-shaped La-Al2O3 is beneficial for inducing atomic-level deposition of Pt / Pd and for the beneficial control of crystal planes, thereby facilitating the efficient treatment of exhaust gas.

[0170] As can be seen from Example 1 and Comparative Example 7, the traditional co-impregnation-sodium borohydride reduction route is difficult to achieve catalytic performance comparable to that of the present invention. Although Comparative Example 7 uses the same La-Al2O3 support and similar amounts of Pt and Pd, Pt and Pd species are more prone to random deposition, rapid reduction, and local aggregation during its preparation process. It is difficult to form a Pd pre-anchored induced Pt colloidal directional deposition structure, and it is also difficult to stably construct the Pt (111 / 200) composite crystal plane, atomic-level noble metal species, and oxygen defect synergistic interface.

[0171] As shown in Example 1 and Comparative Examples 8 and 14, there is a significant synergistic effect between Pt and M metals such as Pd. It is difficult to simultaneously achieve high NO oxidation capacity, low CO / C3H6 ignition temperature, and high C3H8 conversion rate using Pt or Pd alone, indicating that the synergistic loading of Pt and M species is a necessary condition for obtaining highly active catalytic materials.

[0172] As demonstrated by Examples 1 and Comparative Examples 9-11, the defect-confined impregnation method of Pd species plays a crucial role in catalyst performance. Comparative Example 9 did not employ alternating vacuum-atmospheric pressure treatment, Comparative Example 10 did not undergo pulsed ultrasonic treatment, and Comparative Example 11 employed conventional continuous ultrasonic treatment instead of pulsed ultrasonic treatment; their catalytic performance was consistently lower than that of Example 1. This indicates that alternating vacuum-atmospheric pressure treatment facilitates the entry of Pd species into the surface pores of rod-shaped La-Al₂O₃, the interparticle spaces, and the vicinity of oxygen defect sites; pulsed ultrasonic treatment improves the dispersibility of Pd species and increases its contact probability with La–O–Al sites, hydroxyl defect sites, and oxygen vacancy precursors.

[0173] As shown in Example 1 and Comparative Examples 12 and 13, the order of Pt and Pd introduction has a significant impact on the catalyst structure and performance. Comparative Example 12 did not perform Pd pre-anchoring separately, but instead directly added the Pd source to the Pt colloid preparation or deposition process; Comparative Example 13 deposited Pt first and then introduced Pd, and its performance was lower than that of Example 1. This indicates that the two-stage loading sequence of "Pd defect-confined pre-anchoring followed by Pt colloid directional deposition" in this invention is an important condition for constructing a highly dispersed PtM interface structure. Pre-anchoring Pd species near the defect sites on the support can serve as nucleation / anchoring points for preferential Pt colloid deposition and in-situ PtM alloying; if the loading sequence is changed or Pt and Pd are deposited simultaneously, Pt and Pd are prone to random distribution or local aggregation, weakening the synergistic effect between the Pt (111 / 200) composite crystal plane, atomic-level noble metal species, and oxygen defects.

[0174] As shown in Example 1 and Comparative Example 15, excessively high annealing temperatures lead to a decrease in catalytic performance. In Comparative Example 15, after increasing the Ar atmosphere annealing temperature to 300°C, the catalytic performance was lower than that of Example 1, indicating that excessively high temperatures may cause migration and aggregation of some atomic-level noble metal species, reconstruction of the highly active Pt(200) crystal facets, or a reduction in oxygen defect sites. Example 1, using a lower temperature inert atmosphere annealing, can better maintain the Pt(111 / 200) composite crystal facets, atomic-level noble metal species, and interfacial oxygen defect structure while promoting Pt-Pd interfacial diffusion and alloying.

[0175] In summary, the pre-formed rod-shaped La-Al2O3 support, the programmed oxygen potential defect activation thermal modification, the M species defect confinement pre-anchoring, the Pt colloidal directional deposition, and the low-temperature inert atmosphere annealing together constitute the necessary technical solutions of this invention; the Pt / M mass ratio, the Pt colloidal preparation temperature, the deposition pH, the deposition temperature, and the annealing temperature are preferred technical solutions for further optimizing the catalytic performance.

Claims

1. A catalytic material of oxygen-deficient Pt(111 / 200) composite crystal plane atomically supported rod-shaped La-Al2O3, comprising the support and the supported active component, characterized in that, The support is rod-shaped La-Al2O3; The active ingredient is an atomic-level PtM composite material, in which Pt and M exist in the form of nanoparticles, single atoms, diatomic particles and few-atom clusters; and Pt has 111 and 200 composite crystal planes; M includes at least one of Pd, Co, Mn and Cu. The carrier and / or active ingredient have oxygen defects; The preparation steps of the oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3 catalytic material include: Step 1: Rod-shaped La-Al2O3 was thermally modified to obtain a modified support; The aforementioned thermal modification is a programmed variable oxygen potential defect activation thermal modification, which includes a high oxygen atmosphere thermal modification process and a low oxygen atmosphere thermal modification process; wherein, the oxygen content of the high oxygen atmosphere is 10~100v%; and the oxygen content of the low oxygen atmosphere is below 5v%. Step 2: The modified carrier and the M source are impregnated to obtain a carrier composite with M; wherein the impregnation treatment includes a pressure-switching impregnation process and a pulsed ultrasonic impregnation process; wherein the pressure-switching impregnation process includes a periodic impregnation process under pressure P1 and an impregnation process under pressure P2; pressure P1 is negative pressure; pressure P2 is atmospheric pressure or positive pressure; Step 3: The composite M support and Pt colloid were mixed and deposited under alkaline conditions to obtain the composite Pt-M support. Step 4: The catalytic material was prepared by annealing the composite Pt-M support at a temperature of 150~250℃.

2. The catalytic material of oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3 as described in claim 1, characterized in that, In rod-shaped La-Al2O3, the La content is 1~2 wt.%; the diameter is 8~30 nm; and the aspect ratio is 3~8. In PtM composite materials, the weight ratio of Pt / M is 3:1 to 6:1; In the catalytic materials, the loading of PtM composite materials is 0.8~1.6 wt.%; The relative exposure ratio of Pt(200) crystal planes in the catalytic material is 20-30%.

3. A method for preparing a catalytic material of oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3 as described in claim 1 or 2, characterized in that the step include: Step 1: Rod-shaped La-Al2O3 was thermally modified to obtain a modified support; The aforementioned thermal modification is a programmed variable oxygen potential defect activation thermal modification, which includes a high oxygen atmosphere thermal modification process and a low oxygen atmosphere thermal modification process; wherein, the oxygen content of the high oxygen atmosphere is 10~100v%; and the oxygen content of the low oxygen atmosphere is below 5v%. Step 2: The modified carrier and the M source are impregnated to obtain a carrier composite with M; wherein the impregnation treatment includes a pressure-switching impregnation process and a pulsed ultrasonic impregnation process; wherein the pressure-switching impregnation process includes a periodic impregnation process under pressure P1 and an impregnation process under pressure P2; pressure P1 is negative pressure; pressure P2 is atmospheric pressure or positive pressure; Step 3: The composite M support and Pt colloid were mixed and deposited under alkaline conditions to obtain the composite Pt-M support. Step 4: The catalytic material was prepared by annealing the composite Pt-M support at a temperature of 150~250℃.

4. The method for preparing the oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3 catalytic material as described in claim 3, characterized in that, In step 1, the high-oxygen atmosphere is a mixture of air, oxygen, oxygen-dilution gas, or air-dilution gas. The low-oxygen atmosphere is at least one of nitrogen and rare gases; The thermal modification includes a periodic high-oxygen atmosphere thermal modification process and a low-oxygen atmosphere thermal modification process; the time for a single high-oxygen atmosphere thermal modification is 10~60 min; the time for a single low-oxygen atmosphere thermal modification is 10~60 min. The number of cycles for the high-oxygen atmosphere thermal modification process and the low-oxygen atmosphere thermal modification process is 1 to 5. The temperature for thermal modification is 300~500 ℃; The total time for thermal modification is 2 to 4 hours.

5. The method for preparing the oxygen-deficient Pt(111 / 200) composite crystal plane atomically supported rod-shaped La-Al2O3 catalytic material as described in claim 3, characterized in that, In step 2, the M source is a water-soluble salt of metal M and / or a metal M complex; The M source includes at least one of the following: chloride, nitrate, acetate, acetylacetone salt, ammonia complex salt, or organic amine complex of the M metal; The impregnation treatment system also contains complexing agents and slow-release alkali sources; During the impregnation process, the pressure of P1 is -0.06 to -0.10 MPa; The immersion time under P1 pressure is 5~30 min for a single application, and the immersion time under P2 pressure is 5~30 min for a single application. The number of cycles in the pressure-variable impregnation process is 1 to 5. The power of the pulsed ultrasonic impregnation process is 100~500 W, each ultrasonic session lasts 1~10 min, with an interval of 1~10 min, and the cycle is repeated 1~6 times.

6. The method for preparing the oxygen-deficient Pt(111 / 200) composite crystal plane atomically supported rod-shaped La-Al2O3 catalytic material as described in claim 3, characterized in that, Pt colloids are obtained by a reduction reaction of Pt source, alkali and ethylene glycol; The Pt source is at least one of chloroplatinic acid, hydrated chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, platinum nitrate, or platinum acetylacetonate. The alkali is at least one of NaOH, KOH, LiOH, ammonia, sodium carbonate, or potassium carbonate; The weight ratio of Pt source, alkali and ethylene glycol is 1:0.2~3:30~200; The reduction reaction temperature is 120~160℃; The reduction reaction takes 2 to 5 hours.

7. The method for preparing the oxygen-deficient Pt(111 / 200) composite crystal plane atomically supported rod-shaped La-Al2O3 catalytic material as described in claim 3, characterized in that, In step 3, the pH under alkaline conditions is 8.5~10.5; The deposition temperature is 70~90℃; the deposition time is 1~5h.

8. The method for preparing the oxygen-deficient Pt(111 / 200) composite crystal plane atomic-level PtM supported rod-shaped La-Al2O3 catalytic material as described in claim 3, characterized in that, In step 4, the annealing atmosphere is at least one of Ar, N2, and He; the annealing time is 1 to 4 hours. The process includes a pre-annealing step before annealing, wherein the pre-annealing atmosphere is air; the pre-annealing temperature is 80~120℃; and the pre-annealing time is 0.5~2.5h.

9. The application of a catalytic material according to any one of claims 1-2 or a catalytic material prepared by the preparation method according to any one of claims 3-8, characterized in that, It is used for the catalytic oxidation of automobile exhaust.

10. The application as described in claim 9, characterized in that, The vehicle exhaust gas contains at least one gaseous pollutant selected from CO, NO, C3H6, and C3H8.

Citation Information

Patent Citations

  • Diesel exhaust gas oxidation catalyst, and method for purifying diesel exhaust gas by using same

    CN105188916A

  • Diesel oxidation catalyst and preparation method thereof

    CN119951543A

  • Pt cluster catalyst, preparation method and application

    CN120037905A

  • PtM alloy / gamma-Al2O3 catalytic material with oxygen vacancy-dislocation structure, preparation method and application of PtM alloy / gamma-Al2O3 catalytic material and tail gas treatment device

    CN121623782A